Hypertensive load predicts recovery of renal function for patients undergoing revascularisation for renal artery stenosis - Ben Edgar; Rob Pearson; Andrew Jackson; Callum Stove; Ram Kasthuri; Keith Hussey; Christian Delles; Colin Geddes; Patrick Mark; Giles Roditi; Linsay McCallum; David B. Kingsmore (Scientific Reports)
Abstract Renal ischaemia due to renal artery stenosis produces two differing responses - a juxtaglomerular hypertensive response and cortical renal dysfunction. The reversibility of renal impairment is not predictable, and thus renal revascularisation is controversial. This study aims to test the hypothesis that the hypertensive response to renal ischaemia reflects viable renal parenchyma, and thus could be used to predict the recovery in renal function. A retrospective analysis was performed of all patients who had renal revascularisation for renal impairment in a defined geographical area (West of Scotland, population 2.4 million) between 2008 and 2024. Clinical records were used to determine the pre-intervention blood pressure, anti-hypertensive medication load and renal function, and post-intervention outcomes. The Hypertensive Index (HTi), a combined measure of systolic blood pressure and antihypertensive drug load, was used as a measure of pre-intervention hypertensive response. 75 patients had intervention for renal impairment over 15 years (68 endovascular, 7 open). Mean pre-intervention serum creatinine of 323 µmol/L was reduced to 191 umol/L at discharge and 182 µmol/L at 6-month follow-up. Refractory hypertension (HTi > 120) was associated with a significant benefit from revascularisation with improved renal function (p = 0.003) and reduced risk of future dialysis (p = 0.001). Renal impairment with no hypertensive response was highly predictive of the need for future dialysis. The hypertensive index is a good predictor of the impact of renal revascularisation on improving renal function with good outcomes in selected patients, and the absence of this is an indicator of chronic non-reversible renal dysfunction.